[Co(H2O)6]2+ and H3O+ encapsulated in a unique 3D anionic Co(ii) framework with hydrophilic hexagonal and circular channels1. Issue 37 (7th October 2015) - Zhao, Jun; Liu, Bo; Wu, Ya-Pan; Bai, Liang; Zhang, Jian; Li, Dong-Sheng
<x xml:space="preserve">Abstract</x> An interesting Co-based 3D framework exhibits a rare example where [Co(H2O)6]2+ and H3O+ ions not only act as counterions to balance the negatively charged structure, but also may serve as templates in the assembly of the anionic framework with open hydrophilic channels.